THE PLEKHANOV UNIVERSITY DEVELOPMENT AS THE 1st ECONOMIC INSTITUTION OF THE COUNTRY (The 20–30s of the 20th century) - Aleksey I. Samsin (Plekhanov Russian University of Economics, 2017)
The article shows in what way the dramatic restructuring of higher education was carried out in Russia during the first years of Soviet power. Different opinions about possible changes were expressed at meetings and in the press. Some experts proposed to make higher education as close to social and economic practice as possible, others paid attention to the fact that it was necessary to strengthen the military component in higher school. Finally, the position supported by A. V. Lunacharskiy, the first Commissar for Education prevailed. He said that the process of education in universities by its character and orientation should be multi-profile with serious social and economic bias. Education and its different forms should provide professional knowledge and skills and at the same time mould conscious of the new man, his/her moral qualities. Actually he advanced the idea of higher school humanitarization. Its preconditions can be found in pre-revolution education process, however it should be filled with new content. The authors point out that at present the idea of humanitarization is the principle component of higher education.